Estudo da carbonatação natural de concretos com diferentes adições minerais após 10 anos de exposição - Ferreira, Murillo Batista (2013)
Among lots of pathologies that attack the concrete structures stands out the corrosion of the reinforcements, that may be triggered by the phenomenon of carbonation of the concrete, which consists in a physico-chemical process between the carbon dioxide (CO2) from the atmosphere and the cement paste compounds, which has as main result the calcium carbonate precipitation (CaCO3) in a region of the concrete cover, with the formation of a layer that has less alkalinity than that not affected by this phenomenon. The carbonation moves from outside to inside the concrete through a carbonated front, that when it reaches the depth of the reinforcement causes destabilization of the protective passive layer, providing the onset of the corrosion. How many researches are conducted by accelerated carbonation tests, it is of paramount importance that the evaluation process by comparing it with data obtained from samples that have suffered natural carbonation. Facing this reality, this research is conducted based on samples that are exposed in the natural environment (external housed) for a period of ten years, with the general objective of evaluating the results (coefficients and carbonation depths) of natural carbonation process of concrete with different mineral additions, water/binder ratios and curing conditions (moist and dry) over this period. For this realization, samples of concrete produced in 2002, produced in Castro's dissertation (2003). The variables included in the experimental program are: concretes with five types of mineral additions (silica fume (10%), rice husk ash (10%), metakaolin (10%), fly ash (25%), blast furnace slag (65%), these amounts being in partial replacement of cement mass) and the reference concrete, without mineral addition; three water/binder relationships (0.40 , 0.55 and 0.70) and two curing conditions (moist and dry). Measurements were made of natural carbonation through of pH indicator based on phenolphthalein, elaborating a database along time, through measurements with periods of exposure of 0.25 years (91 days), 0.50 years (182 days), 0.82 years (301 days), 3 years, 7 years, 9 years and 10 years, allowing comparative performance evaluation of various concrete containing mineral additions, taking as a base carbonated depths and natural carbonation coefficients data. The results showed that there are significant differences of behavior between different concretes studied and that in the overall analysis of the carbonation natural coefficients, the reference concrete showed the best alone performance, showing that the alkaline reserve is still the predominant effect in terms of against carbonation, but the microstructure refinement provided by additions (physical effect) approaches such chemical aspect, as detected, for example, in concrete with metakaolin. In the correlation between the accelerated carbonation coefficients and the natural carbonation ones, was verified a relation of direct proportionality between the coefficients found for the two procedures, with the coefficient signifying accelerated approximately 7.4 times the natural ratio. The useful life predictions showed periods of time until the carbonation front reaches the cover thickness ranging from 4 years up to 241 years, for the different concretes and situations analyzed.